Child acceptability of a novel provitamin A carotenoid, iron and zinc-rich complementary food blend prepared from pumpkin and common bean in Uganda: a randomised control trial - Edward Buzigi; Kirthee Pillay; Muthulisi Siwela (BMC, 2020)
Abstract Background Ugandan children are fed homemade complementary foods (CFs) which are usually deficient in vitamin A, iron and zinc. Novel homemade CFs rich in vitamin A, iron and zinc need to be developed, and assessed for their acceptability among target children. Objective Homemade provitamin A carotenoids (PVACs), iron and zinc-rich complementary food (CF), common bean pumpkin blend (BPB) formulated from pumpkin (Sweet cream) and common bean (Obwelu) and PVAC-rich pumpkin blend (PB) from Sweet cream were prepared by expert peer mothers. This study compared child acceptability of BPB and PB (control). Methods The crossover acceptability study randomly assigned Ugandan children 6 to 24 months old to either receive 100 g of BPB (n = 35) or 100 g of PB (n = 35) on day one. After a washout period of one day, children crossed over to receive either BPB (n = 35) or PB (n = 35). The amount of CF consumed, duration of consumption, and micronutrient intake were assessed. The CF was acceptable if children consumed ≥50 g (50%) of served food (100 g). A paired t-test was used to determine the mean differences within participants between BPB and PB. The level of statistical significant difference was set at a probability value of 5% (p = 0.05). Results The mean consumption of BPB and PB was 53.9 g and 54.4 g, respectively. The mean duration for consumption of BPB and PB was 20.6 and 20.3 min, respectively. There was no significant difference in the amounts consumed, and duration of consumption in BPB and PB (p > 0.05). The mean intake of vitamin A was significantly higher (p < 0.00001) in PB (152.5 μgRAE) compared to BPB (100.9 μgRAE). The mean iron intake was significantly higher in BPB (1.1 mg) (p < 0.00001) compared to PB (0.3 mg). Furthermore, zinc intake was significantly higher (p < 0.00001) in BPB (0.58 mg) compared to PB (0.13 mg). Conclusion A homemade complementary food, BPB, made from locally available common bean and pumpkin is rich in PVACs, iron and zinc and is acceptable to children in the age range of complementary feeding in Uganda. Trial registration Pan African Clinical Trials Registry www.pactr.org as PACTR202002576768667 . Retrospectively registered. Date of registration: 29/January/2020.